Ned Kelly under the microscope : solving the forensic mystery of Ned Kelly's remains - Cormick, Craig; CSIRO (Collingwood, Victoria : CSIRO Publishing, 2014)
Do we really need another Ned Kelly book? After all, his story is a part of Australian folklore and his legend has been captured in movies, books and paintings. The answer is yes, as this book is unique. It is a rigorous look at the forensic science behind investigations into Ned Kelly. In 2009 the remains of Ned Kelly were dug up at Pentridge Prison and identified after an exhaustive forensic analysis by the Victorian Institute of Forensic Medicine. Analysing a skeleton more than 130 years old involved processes such as DNA extraction, 3D facial reconstruction, and identifying the skeleton by its injuries. However in 2011 the Victorian government announced that while it had identified the remains of Ned Kelly, the skull long thought to be his, was not, and so another twist in the scientific tale began. Along with an exploration of the forensic analysis, this book unpicks some of the Kelly myths: Was Ned Kelly illiterate? Did Ned Kelly have a daughter? It sheds light on more recent urban myths does such as having a Ned Kelly tattoo puts you at risk of dying violently? The identification of the remains of Ned Kelly is a remarkable story and definitely one worth telling.
Includes bibliographical references and index.
Keywords: Kelly, Ned, -- 1855-1880 -- Death and burial; Bushrangers -- Australia -- Biography; Forensic sciences -- Case studies; Forensic osteology -- Case studies; Human remains (Archaeology) -- Victoria; Excavations (Archaeology) -- Victoria; Australian; Modern history (c 1788-1914); Crime & criminology; Forensic science